O Golpe (Impeachmemt) de 2016: a intensificação da intolerância no Brasil - Bokany, Vilma Luiza (2022)
This work proposes to discuss intolerance in Brazil, starting with the 2016 coup, having as a starting point the 2013 demonstrations and their consequences in the evaluation of public opinion, which culminated in the weakening of the government, facilitating the 2016 parliamentary coup. intolerance in this period appears and worsens as new political configurations access the government. The main projection of intolerance is directed to the figure of former president Dilma Rousseff, constantly treated in a pejorative way. The intolerance that is misogyny extrapolates and extends to every female gender, especially to women who work in the field of politics. In addition to the figure of women, blacks, poor and peripheral, homosexuals and indigenous, historical victims of intolerance in Brazil, became the target of hate speeches that were born in this period. The hypothesis is that in addition to the hatred of the PT, as a political party, or of leftist ideas, the intolerance present in the demonstrations in São Paulo also expresses a certain class hatred, against the poor, blacks, women and homosexuals. In addition to removing the PT from power, the coup also intended to reduce the possibility of disseminating reparatory policies to this public, instituted mainly by the Ministry of Women and SEPPIR (Special Secretariat for Policies for Racial Equality). As soon as former President Dilma was removed from office, the provisional government of Michel Temer incorporated the Ministry of Human Rights, SEPPIR and the Ministry of Women into the Ministry of Justice, reducing priorities to these population segments, contributing to the maintenance of inequalities and, removing the possibility of the rise of a new social layer that emerged in the years of PT government, threatening to approach the middle class. To understand this recent process, it was essential to read the current bibliography, produced in Brazil after the coup, by authors such as Jessé de Souza, Esther Solano, André Singer, among others, and we followed the development of intolerance manifestations through articles by newspapers, websites and magazines, reported from 2013 to 2016, and in the period immediately after the impeachment (2016) through the 2018 elections, to the present day. To understand the intersectionality between gender, class and income, it was important to resort to concepts from Patrícia Hill Collins, Angela Davis, Judith Buttler, Achille Mbembe, Luís Felipe Miguel and Flávia Birolli, Lilia Schwarks, Tiaraju Pablo D' Andrea and Sílvio Almeida, among others